On the accuracy of permittivity profile inversion - Oweijane, Frederic; Ahmad, Falih (Microwave and optical technology letters, 2021)
An inversion accuracy improvement technique based on the two‐port network subject taken from the microwave theory is presented. The technique is dedicated to the one‐dimensional dielectric structure where the permittivity is a function of depth. Optimization and discretization procedures are part of this technique. Applicability and validity of the technique is demonstrated through numerical experiments.